(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: achieving Human Papilloma Virus (HPV) - related diseases control is an important challenge in public health. In Italy HPV vaccination uptake does not rise a sufficient level. The aim of this project is to identify strategies to promote HPV vaccination in Italy. Methods: an integrated approach consisting of a systematic review and a two-step panel consultation was used to identify strategies to increase vaccination uptake among adolescents, population target of the national vaccination program, and to promote vaccination in additional targets. Overall, ten experts in the fields of Gynecology, Public Health, General Practice and Pediatrics were involved along with Patients representatives. Recommendations were elaborated according to a set of criteria drawn from the Evidence to Decision (EtD) framework. Results: the systematic review led to the identification of three categories of strategies: reminds, education and multicomponent approaches respectively. A strong recommendation was formulated to use reminds tailored to vaccine recipients or their parents, and a moderate recommendation to use reminds directed to health professionals. A moderate recommendation was developed on the implementation of multicomponent interventions. A strong recommendation was yielded with respect to the promotion of HPV vaccination among women already treated for HPV-related diseases, fertile women not previously vaccinated and 25 year-old women undergoing cervical cancer screening. Lastly, a strong recommendation was formulated for catch-up initiatives targeted to women and men turning 18 years of age. Conclusion: this project led to the identification of several valuable strategies to improve HPV vaccination and strengthen HPV-related diseases control at national level.